Die Fußnote über Geognosia in Humboldts Florae Fribergensis specimen - Knobloch, Eberhard; Pieper, Herbert (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2007)
Abstract Humboldt distinguished between three disciplines dealing with the inquiring of the earth: geognosia, historia telluris, physiografia. In 1793, he used the notion of “Geognosie” for the first time. He explained the notion in a footnote that was reprinted in 1815, 1817, and again in 1845. The paper analyses the meaning attributed by Humboldt to the notion of “Geognosie” and gives a new German translation of the Latin texts of the footnote. Zusammenfassung Humboldt unterschied zwischen drei Gebieten, die sich mit der Erfassung der Erde befassen: geognosia, historia telluris, physiografia. 1793 verwandte er den Begriff „Geognosie“ zum ersten Mal. Er erläuterte den Begriff in einer Fußnote, die 1815, 1817 und 1845 erneut abgedruckt wurde. Der Aufsatz untersucht die Bedeutung, die Humboldt dem Begriff „Geognosie“ beilegte, und bietet eine neue deutsche Übersetzung der lateinischen Texte der Fußnote.